Endonasal dacryocystorhinostomy without stents: our experience - Raga, Preeti S.; Waghre, Amrith Laal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Dacryocystorhinostomy (DCR) for the treatment of nasolacrimal duct obstruction. The aims of the study were to assess the patency rate of endoscopic (ED DCR) using a technique similar to that described by McDonogh and Meiring but without the use of nasolacrimal silicone stents. Methods: Endonasal dacryocysto-rhinostomies (ED DCRs) were performed without the use of silicone stents in 46 patients (20 male, 26 female). These patients were followed up for an average of eight months. Results: The procedure was successful in 86.95% of cases as measured by patient’s relief of symptoms and endoscopic visualization of a middle meatal ostium draining the lacrimal sac. Conclusions: In our study ED DCR without stents had less complications and also a success rate of 86.95% achieved when compared with DCR with stents.